A Comparison of Readmission Rates in Heart Failure with Preserved Ejection Fraction (HFpEF) V/S Heart Failure with Reduced Ejection Fraction (HFrEF): Heart Failure with Preserved V/S Reduced Ejection Fraction - Ishaque Shaikh, Salman; Ahmed, Zuhaib; Ahmed , Sumair; Kafeel Meo, Angabeen; Rehman, Adeel Ur; Baqai, Lubna; Ali, Muhammad; Yaqoob, Samina (Pakistan Journal of Health Sciences, 2022)
Heart failure (HF) contributes to increased hospital readmissions which results in amplified resource burden and morbidity. The conditions of readmission in HF patients have not been clarified. Objectives: To govern the relationship between heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction and correlation with readmissions ratio. Methods: This prospective cohort study was held in the Adult Cardiology department of Tabba Heart Institute, Karachi, Pakistan for 6 months from March 10, 2019 to September 9, 2019. After attaining informed consent, an interview and clinical examination were performed and subjects were divided into exposed and unexposed groups (HFpEF and HFrEF). Patients were followed for readmission within one-month of initial hospitalization. Results: A total of 162 patients with heart failure (81 patients in each group) were included in the study. The mean total age was 65.4 ± 10.4 years, and 52.5% of the patients were male. Rehospitalization on day 30 was observed in 11 (13.6%) patients from the Group A (HFpEF) and in 10 (12.3%) patients from the Group B(HFrEF). Cardiac readmission was more common in the unexposed group than in the exposed group (80.0% vs. 63.6%). Conclusions: After admission due to acute heart failure, patients with HFpEF have a statistically insignificantly higher hospitalization burden compared to patients with HFrEF. In addition, patients with HF with preserved ejection fraction were as likely to be readmitted for cardiovascular reasons as those with HF with reduced ejection fraction.